Comparison of Growth and Primary Shunt Product Formation by Claviceps purpurea Cultured on Succinic Acid and Glucose as Carbon Sources - Taber, W. A. (1966)
Growth on a medium containing succinic acid as the sole carbon source produced 1 g (dry weight) of mycelium per liter of medium by 50 days of incubation, whereas 25 g of mycelium was produced in 10 days when glucose was also present in the medium. Primary shunt metabolism took place during growth on succinic acid in spite of the extremely slow growth. Mycelia grown on succinic acid contained a higher percentage of residual mycelium and phosphate, but a lower percentage of mannitol, carbohydrate, lipid, and water-soluble nitrogen, than mycelia grown on a mixture of glucose and succinic acid. Thus, although primary shunt metabolism is favored by rapid growth on a rich, balanced sugar medium, it can also take place during extremely restricted growth in a medium containing succinic acid as the sole carbon source.